2020
DOI: 10.1017/s0898030619000265
|View full text |Cite
|
Sign up to set email alerts
|

Interagency Cooperation in the Twilight of the Great Society: Telemedicine, NASA, and the Papago Nation

Abstract: Abstract:NASA has put people in unique and extreme environments for over six decades. Supporting these individuals with a comprehensive health-care system has evolved over this period. As the Apollo program ended and NASA began to contemplate a space shuttle and space station program, societal pressures in the late 1960s and early 1970s caused federal agencies such as NASA to reconsider how to link the needs of the space program with a growing pressure to address societal needs by forging interagency partnersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Virtual care, commonly defined as medical care delivered at a distance by means of technology, has existed since the 1970s. 1 Despite substantial interest and investment in virtual care by both the federal and provincial governments, 2 – 4 widespread adoption was modest. 5 , 6 Research suggested that barriers to virtual care uptake in Ontario before the pandemic included limited physician reimbursement and government mandates that virtual visits use an approved video platform.…”
mentioning
confidence: 99%
“…Virtual care, commonly defined as medical care delivered at a distance by means of technology, has existed since the 1970s. 1 Despite substantial interest and investment in virtual care by both the federal and provincial governments, 2 – 4 widespread adoption was modest. 5 , 6 Research suggested that barriers to virtual care uptake in Ontario before the pandemic included limited physician reimbursement and government mandates that virtual visits use an approved video platform.…”
mentioning
confidence: 99%
“…Gonçalves et al (2018) defendem que a utilização de TICs em saúde traz desenvolvimento à prática médica, abrindo oportunidade para oferta de novos serviços a distância em especial o atendimento e monitoramento domiciliar dos pacientes. Alguns autores apontam que a utilização de telediagnósticos por imagem, videoconferências médicas e trabalhos colaborativos de segunda opinião resultam em um aumento da acessibilidade de serviços especializados em saúde para uma grande parcela da sociedade, contribuindo na prevenção e tratamento das diversas patologias (Santos, 2017;Gonçalves et al, 2018;Simpson, Doarn & Garber, 2020).…”
Section: Tecnologias Digitais Em Saúde E a Relação Médico Pacienteunclassified
“…This wide attention, if not viral media coverage, is helping the general public understand the health effects of prolonged isolation and confinement as well as medical and lifestyle countermeasures for it [ 39 , 40 ]. Such research in NASA also sheds light on challenges of the elderly who are aging in place [ 41 , 42 ]. The COVID-19 pandemic is bringing elder care out of the shadows because of severe impact on this population and because it is providing everyone else direct experience with some of the social and cognitive challenges faced by the elderly including the need for continual adaptation and resilience.…”
Section: Implications For Lifestyle Interventions In the Medical Homementioning
confidence: 99%